Retention of medical organization personnel in rural areas - Alimkulov, A.M.; Maukenova, A.A. (BUKETOV BUSINESS REVIEW, 2024)
Object: This article aims at a comprehensive analysis of the effectiveness of existing measures and the development of advanced strategies to improve the retention of medical personnel in rural areas of Kazakhstan, with an emphasis on analyzing programs and initiatives, identifying factors affecting staff retention, and developing improved retention strategies. Methods: The study included two electronic searches in Medline (via PubMed) to identify qualitative studies on factors affecting the retention of doctors in rural areas, as well as a questionnaire survey of medical workers of KGP "Amangeldinskaya RB". Data collection methods were used, including literature reviews, surveys. Findings: The study showed that staff retention in rural areas can be improved through comprehensive strategies including improving working conditions, increasing pay levels, providing educational opportunities and infrastructure. It was found that there is a high demand for specialists of certain medical profiles, and the uniform age composition of the staff indicates potential stability in the staff. Conclusions: The sustainability and quality of medical care in rural regions directly depend on the effectiveness of staff retention strategies. It is recommended to pay special attention to improving working conditions, increasing salaries and creating favorable conditions for professional and personal growth.